Open, Flexible and Distance Learning in a Post-Truth World - Alison Fields; Maggie Hartnett; Niki Davis (Flexible Learning Association of New Zealand, 2017)
The times they are a-changin'. It's a prophetic song, and one that's been around long enough to attest to times that are always changing, as very little stands still for long. In this Editorial there are many changes noted, including changes in the editorial team, changes in the profile of this Journal, and a look at changes in the way open, flexible and distance learning is both given and received in the post-truth world. Increased skills in information literacy and digital literacy have become fundamental in this new landscape, enabling able learners to navigate their way in this 'new' world with an open mind and a critical eye. There will be changes for educators as well, as we try to manage teaching and learning in this new educational setting.